Mnisi jako „żołnierze” Chrystusa w nauczaniu Jana Chryzostoma. Analiza 69. i 70. homilii z cyklu "Homilie na Ewangelię według św. Mateusza" - Szczur, Piotr (Vox Patrum, 2015)
This article considers the subject of spiritual warfare led by monks as the “soldiers” of Christ. Author of the article analyzed two John Chrysostom’ homilies (69 and 70) from the series Homily on the Gospel according to St. Matthew. First, he emphasizes the important role of the monasticism in the life and thought of John Chrysostom already from the beginning of his literary activity. Then, on the basis of sources, he shows the monks as a “spiritual army” of Christ, who are staying at the hermitage instead of at a military camp, and instead of arms have ascetic practices. This spiritual army of Christ refers more splendid victory than the crack troops of the Roman Empire army, because the battle with the demons is far more difficult than fighting with people. In the final part of the article pointed out the profile of pastoral teaching of John Chrysostom, who encouraged all Christians to take spiritual warfare as the monks.